2012
DOI: 10.4028/www.scientific.net/msf.727-728.727
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Bone Processing for Biofilter Application

Abstract: This work involves the processing of bovine bone for use as biofilter collector of heavy metals in water. Before processing, it was necessary to clean the bone selected for removing the organic material adhered thereto. Drying was done in weathered during 18 days. Then the bones were calcined at a constant temperature of 750°C for 6 hour. The bone grinding was performed by means of an analytical mill in order to obtain a finer grain size. Once processed, the bovine bone powder was characterized by X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The composition of cortical tissue is a combination of various materials, including hydroxyapatite mineral [ 30 ], organic components, and water [ 31 , 32 ]. The XRF method has shown that bone tissue comprises calcium, phosphorus, potassium, and other elements in trace amounts [ 33 ]. The basic building blocks of cortical bone tissue are osteons, which are elliptical cylinders with a diameter of 100–300 µm and a length of 3–5 mm [ 34 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The composition of cortical tissue is a combination of various materials, including hydroxyapatite mineral [ 30 ], organic components, and water [ 31 , 32 ]. The XRF method has shown that bone tissue comprises calcium, phosphorus, potassium, and other elements in trace amounts [ 33 ]. The basic building blocks of cortical bone tissue are osteons, which are elliptical cylinders with a diameter of 100–300 µm and a length of 3–5 mm [ 34 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Parameters of the sorption experiments are given in Table 1 where C 0 and C e refer to initial and equilibrium concentrations, respectively, and NM is not measured. It can be noticed that almost complete sorption of lanthanide ions was achieved only at concentrations lower than 5•10 -4 mol/dm 3 . An increase of the lanthanide ions concentration above this level resulted in a gradual decrease of sorption efficiency (Fig.…”
Section: Sorption Efficiency Of Ln 3+mentioning
confidence: 98%
“…The mesopore volume share was 71% and the average pore diameter (L AV ) was 3.08 nm. From the intrusion curve, the mercury intrusion porosimetry provided the following information on BHAP sample: the total intrusion volume was 0.6196 cm 3 /g, total pore area 2.063 m²/g, median pore diameter (volume) 3.1638 µm, median pore diameter (area) 0.4025 µm, average pore diameter (4 V/A) 1.2012 µm, bulk density at 0.0036 MPa 0.9685 g/cm 3 , apparent (skeletal) density 2.4216 g/cm 3 and porosity 60.0%. The FTIR spectrum of BHAP is shown in Fig.…”
Section: Physicochemical Characteristics Of Prepared Bhapmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, hydroxyapatite (HA) considered a bioceramic material, which has been produced from natural sources and synthesized from high purity precursors for bone implant applications 14 . Its applications in environmental biotechnology areas are increasingly drawing attention of researchers, mainly to eliminate heavy metals and other toxic materials from superficial waters and soil 15 . Most of the work found report the applications of the synthetic HA 2-4;16 , but few works report the use of natural HA [14][15] , mainly the HA from bovine bone.…”
Section: Introductionmentioning
confidence: 99%